KORELASI ANTARA MOTIVASI BELAJAR DENGAN HASIL BELAJAR PADA MASA PANDEMI COVID – 19 KELAS V - Kristian Kristian; Tahmid Sabri; Rio Pranata (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to describe the correlation between learning motivation and thematiclearning outcomes during the covid-19 pandemic for fifth grade students at 33 NorthPontianak State Elementary School. The method used is a descriptive method in theform of relationship studies by using correlation studies. This study used a populationof 68 students and a sample of 34 students. Data collection techniques used in thisresearch are indirect communication techniques and documentary study techniques.The tools used to collect data are questionnaires and student learning outcomesdocuments. Based on statistical analysis using the product moment correlationformula for calculating the correlation of learning motivation with thematic learningoutcomes during the Covid-19 pandemic, fifth grade students of the 33 NorthPontianak State Elementary School obtained rcount of 0.279, while rtable of 0.339,this means rcount < rtable. From the results of the calculations, it can be concludedthat there is no positive correlation between learning motivation and thematiclearning outcomes during the Covid-19 pandemic for fifth grade students at the 33North Pontianak State Elementary School.Keywords: Correlation, Covid-19, Motivation, Thematic Learning Outcomes